Use of Continuous Glucose Monitoring in Patient with Coronary Artery Disease and Type 2 Diabetes Mellitus: Case Report - Mankovsky, Georgy B.; Dzhun, Yana Yu.; Marushko, Yevhen Yu.; Saienko, Yanina A.; Rudenko, Nadiya M.; Mankovsky, Boris M. (Ukrainian Journal of Cardiovascular Surgery, 2022)
We present a clinical case of continuous monitoring in a patient with coronary artery disease and concomitant type 2 diabetes mellitus. A 75-year-old patient with a history of coronary artery bypass graft surgery more than 10 years ago was admitted to the Ukrainian Children’s Cardiac Center, Clinic for Adults with complaints of angina pectoris. The patient had progressive atherosclerotic lesions of the coronary arteries despite of controlled risk factors (normal weight, regular monitoring of blood pressure, lipid profile, blood glucose and glycated hemoglobin [HbA1c], active lifestyle). The heart team decided to perform percutaneous coronary intervention which resulted in thrombolysis in myocardial infarction (TIMI) 3 flow. During continuous glycemic monitoring in the patient we detected nocturnal asymptomatic episodes of hypoglycemia. Together with endocrinologist we performed adjustment of drug treatment: the hypoglycemic drug sulfonylurea was changed to a sodium-glucose cotransporter 2 inhibitor. Three months later we repeated monitoring of glycemia and no episodes of hypoglycemia were detected, HbA1c was 6.4%. Conclusions. This case report shows that continuous glucose monitoring is an optimal method for diagnosing silent episodes of hypoglycemia and should be considered along with the control of the HbA1c level as an important auxiliary method for controlling type 2 diabetes mellitus in patients with cardiovascular diseases. Because glucose-lowering drugs such as sulfonylureas are risk factors for hypoglycemic episodes in patients with coronary artery disease, they should be changed to more effective and safer medications if possible.